The EIB circular economy guide (European Investment Bank, 2023)
The EIB Circular Economy Guide highlights the need and rationale for a circular economy transition, with the aim of inspiring circular change. The guide presents how the EIB supports the circular economy through financing, advisory and awareness raising. It is regularly updated in response to our evolving understanding of circular economy needs and opportunities, reflecting changes in the policy framework.